Official ERS technical standards: Global Lung Function Initiative reference values for the carbon monoxide transfer factor for Caucasians - Stanojevic, S.; Graham, B.; Cooper, B.; Thompson, B.; Carter, K.; Francis, R.; Hall, Graham (European Respiratory Society, 2017)
© ERS 2017. There are numerous reference equations available for the single-breath transfer factor of the lung for carbon monoxide (TLCO); however, it is not always clear which reference set should be used in clinical practice. The aim of the study was to develop the Global Lung Function Initiative (GLI) all-age reference values for TLCO. Data from 19 centres in 14 countries were collected to define T LCO reference values. Similar to the GLI spirometry project, reference values were derived using the LMS (lambda, mu, sigma) method and the GAMLSS (generalised additive models for location, scale and shape) programme in R. 12660 TLCO measurements from asymptomatic, lifetime nonsmokers were submitted; 85% of the submitted data were from Caucasians. All data were uncorrected for haemoglobin concentration. Following adjustments for elevation above sea level, gas concentration and assumptions used for calculating the anatomic dead space volume, there was a high degree of overlap between the datasets. Reference values for Caucasians aged 5-85 years were derived for TLCO, transfer coefficient of the lung for carbon monoxide and alveolar volume. This is the largest collection of normative TLCO data, and the first global reference values available for TLCO.